A indissociabilidade entre ensino, pesquisa e extensão na educação a distância: análise a partir dos processos de institucionalização da modalidde em universidades federais - Marcela Rosa de Lima Machado (2022)
The goal of this dissertation is to analyze the principle of the inseparability among teaching, research and extension in Distance Learning (DL) based on the perspective of the institutionalization of this modality in Brazilian federal universities. Using quantitative and qualitative methods, this exploratory research aims to: (1) map out the federal universities that offer DL undergraduate programs under the parameters of the Brazilian Open University System (UAB); (2) identify and analyze the parameters involved in their institutionalization’s processes; (3) verify the availability of research and extension in DL programs; and (4) be able to quantitatively understand the relationship between institutionalization and the promotion of inseparability among teaching, research and extension in distance learning. Semi-structured interviews were conducted with UAB’s coordinators and administrators of the federal universities’ departments offering DL programs. The arguments and discussion in this dissertation contemplated authors that analyze public policies for higher education and DL in social, political, and economic contexts in Brazil. It is considered that the inseparability among teaching, research and extension is a principle that should also be extended to DL. This would enable a more critical academic education that might break with the market-centric logic that has historically guided the offering of DL programs. The quantitative research includes feedback from 81.6% of the federal universities offering active DL programs as part of the UAB system, distributed through all the geographical regions of the country. The analysis of the data has shown that the majority (65%) of the universities that participated in this study rely on the financing provided by the UAB system. Interview findings include that the UAB system has been singled out as one of the biggest challenges for institutionalization, putting in check universities’ autonomy. Regarding the inseparability among teaching, research and extension in distance learning, 65% of the participating universities believe that this inseparability has been only partially guaranteed. In contrast, 22.5% of the universities believe it has been fully guaranteed whereas 12.5% believe that it has not been guaranteed at all. The interview data points to the fragility of this principle in DL, especially regarding institutional and financial difficulties of implementing scholarships and funding for teaching, research and extension for DL students. The analyses conducted have shown that the institutionalization of the modality and independence of the UAB system are processes necessary to effectively guarantee the inseparability among teaching, research and extension in Distance Learning.